Acute Kidney Injury Due to COVID-19 in Intensive Care Unit: An Analysis From a Latin-American Center - Neves, Precil Diego Miranda de Menezes; Sato, Victor Augusto Hamamoto; Mohrbacher, Sara; Ferreira, Bernadete Maria Coelho; Oliveira, Érico Souza; Pereira, Leonardo Victor Barbosa; Bales, Alessandra Martins; Nardotto, Luciana Loureiro; Ferreira, Jéssica Nogueira; Machado, David José; Bassi, Estêvão; Silva-Júnior, Amilton; et al. (Frontiers in Medicine, 2021)
Introduction: The kidney may be affected by coronavirus (COVID-19) in the setting of acute kidney injury (AKI). Data about AKI in Intensive Care Unit (ICU) patients of Latin-America are scarce. We aimed to evaluate the risk of AKI, dialysis (HD) and death in ICU COVID-19 patients in a Brazilian center. Methods: Analysis from medical records of COVID-19 patients in a brazilian center. Results: A total of 95 patients were analyzed. There was male predominance (64.2%), median age: 64.9 years, previous history of hypertension and diabetes in 51.6% and 27.4% respectively. AKI was diagnosed in 54 (56.8%) patients and 32 (59.2%) of them required HD. Mortality rate was 17.9%. AKI patients when compared to no-AKI were more frequently hypertensive/diabetic and needed more often organ support therapies. Workups depicted more anemia, lymphopenia, and higher levels of inflammatory markers and higher mortality. Comparing patients who undergone death to survivors, they were older, more frequently diabetic, worse SAPS3 and SOFA scores and need for organ support therapies, AKI and dialysis. Multinomial logistic regression revealed that hypertension (p=0.018) and mechanical ventilation (p=0.002) were associated to AKI; hypertension (p=0.002), mechanical ventilation (p=0.008), and use of vasopressor (p=0.027) to HD patients; and age >65 years (p=0.03) and AKI (p=0.04) were risk factors for death. Conclusions: AKI was a common complication of ICU COVID-19 patients, and it was more frequent in patients with hypertension and need of organ support therapies. As well as age >65 years, AKI was an independent risk factor to death.